Learner's English-Turkish mathematical dictionary - Lapuzina, O.; Veliev, E.; Romanov, Yu.; Romanova, O. (ТОВ "Форт", 2020)
This dictionary contains terminological units on main sections of Mathematics included in the program of pre-university training for international students. Basic mathematical terms are illustrated using examples and figures. Learner’s dictionary is intended for both international students studying Mathematics in English according to the pre-university training program, and for those studying Mathematics at the main faculties of universities. The dictionary can also be useful to mathematicians, methodologists, researchers, and translators.
Keywords: foreign students; terminological units; pre-university training